Is mother condition related to offspring condition in migratory caribou ( Rangifer tarandus) at calving and weaning? - Taillon, J.; Brodeur, V.; Festa-Bianchet, M.; Côté, S.D. (Canadian Journal of Zoology, 2012)
Maternal characteristics can affect offspring traits, yet they are seldom included when considering density dependence of juvenile traits and population dynamics. We quantified the influence of population size and maternal traits on body condition of migratory caribou ( Rangifer tarandus (L., 1758)) calves at birth and weaning. We contrasted female–calf pairs of the Rivière-George (RG) herd, which has recently declined to low population size, with pairs of the much larger Rivière-aux-Feuilles (RAF) herd. Calves of the RAF herd were lighter, smaller, and leaner than calves of the RG herd at both birth and weaning. Differences between herds, however, were much greater at weaning than at calving, suggesting a combined effect of herd size and summer range conditions on calf growth. Maternal mass was positively related to calf body condition during both periods. The positive influence of maternal mass on calf body condition was greater for RAF than RG calves at birth, but it was similar for the two herds at weaning. Our results show that the negative effect of population size on calf body condition can be modulated by maternal mass at calving, and that the positive effect of maternal mass is greater at weaning.